Pengaruh Kompetensi Terhadap Kinerja Karyawan Pada PT Rejeki Bukit Separi - darwis, ady tri anggara; Karhab, Rinda Sandayani; ., Jubaidi (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The main issue faced by PT Rejeki Bukit Separi, a manpower provider in the mining sector, is the suboptimal performance of its employees, characterized by low work quality, delayed task completion, and reduced work effectiveness. This problem is suspected to be closely related to the level of employee competence, particularly in terms of technical understanding, operational skills, and professional attitude. This study aims to analyze and empirically examine the effect of competence on employee performance. A quantitative explanatory survey method was employed. The population consists of all operational employees at PT Rejeki Bukit Separi, totaling 66 respondents selected through a saturated sampling technique. Data were collected using a closed-ended questionnaire with a five-point Likert scale, supported by observation and documentation. Data analysis was conducted using validity and reliability tests, classical assumption tests, and simple linear regression with SPSS version 25. The results show that competence which includes knowledge, skills, and attitude has a positive and significant effect on employee performance. The regression coefficient value is 0.973 with a significance level of 0.000 (< 0.05), and the coefficient of determination (R²) is 0.530, indicating that competence explains 53% of the variation in performance. These findings emphasize the importance of structured competency development programs to enhance productivity and ensure operational safety in the mining industry.